Age, gender, and etiology differences of sports-related fractures in children and adolescents: A retrospective observational study. Issue 4 (January 2019) - Wang, Hongwei; Liu, Huan; Wu, Jun; Li, Changqing; Zhou, Yue; Liu, Jun; Ou, Lan; Xiang, Liangbi
Abstract : Abstract: To investigate the age, gender, and etiology differences of sports-related fractures in children and adolescents (6–18 years old). We retrospectively reviewed 410 child and adolescent patients (335 males and 75 females aged 13.5 ± 3.1 years old) with sports-related fractures admitted to our university-affiliated hospitals from 2001 to 2010. The incidence and pattern were summarized with respect to different age groups, genders, etiologies. Playing basketball (97, 23.7%) and running (90, 22.0%) were the most common etiologies. Radius (102, 24.9%) was the most common fracture site. The most common etiologies and fracture sites were biking (19.6%) and humerus fractures (28.0%) in the ⩽12 age range group, playing basketball (34.0%) and radius fractures (26.2%) in the 12–15 age range group, playing basketball (31.7%) and radius fractures (23.0%) in the 15–18 age range group. The most common etiologies were playing basketball (27.5%) in the male group and running (24.0%) in the female group. The male presented with significantly higher rate of radius fractures and nerve injury, significantly lower rate of femoral fractures than the female. The most common fracture sites were radius fractures in the basketball group (28.9%) and cricket group (37.5%), humerus fracture in the running group (20.0%), biking group (23.3%), and climbing group (45.0%), tibia fractures in the football group (28.9%) and playing SP bars group (50.0%), and ulna fractures (37.5%) in the ice skating group. Sports-related fractures are common in children and adolescents, particularly in males. Basketball, running, and biking were the most common etiologies; radius, ulna, and humerus were the most common fracture sites.